Review of the unprecedented impact of the COVID-19 pandemic on the occurrence of eating disorders. Issue 6 (5th August 2022) - Meier, Karien; van Hoeken, Daphne; Hoek, Hans W.
Abstract : Purpose of review: To review the recent literature on the impact of the coronavirus disease-2019 (COVID-19) pandemic on incidence and severity of symptoms of eating disorders (EDs). Recent findings: A worrying increase of EDs in- and outpatients has been reported since the COVID-19 pandemic began in 2019/2020. Restrictions implemented during the pandemic to protect populations against COVID-19 increased the risk for onset and for worsening of EDs by disrupting eating and exercise routines, social isolation, lack of support, and limited access to healthcare. Substantial increases since the start of the pandemic have been reported for overall incidence (15%), hospital admissions (48%) and emergency department visits (11%) for EDs, with even higher increases among women and children or adolescents with an ED. During the pandemic, ED patients reported increased severity of ED-specific symptoms and increased anxiety, depression and suicidal ideations and -attempts. Treatments shifted largely toward online methods for continuity of care, despite concerns about the quality of care provided and difficulties in self-monitoring. Our review provides preliminary evidence for a similar effectiveness of online treatment to prepandemic face-to-face treatment. In-person assessment remains essential for detecting EDs and for those requiring medical admission. Summary: Although the ongoing COVID-2019 pandemic affected mental health globally, research shows that it particularly affected individuals with an ED diagnosis or at risk for an ED, especially women, children and adolescents, and those with anorexia nervosa.